Implementation of motor current signature analysis as a reliable monitoring system / A. Gheitasi, Mahmoud Moghavvemi and Rosli Omar - Gheitasi, A.; Moghavvemi, Mahmoud; Omar, Rosli (UiTM Press, 2008)
The strategy of Motor current signature has widely been used in industry to diagnose motors faulty conditions. This strategy has some shortcomings that limit it as an engineering auxiliary tool. The main problem of this strategy is its low reliability that in fault diagnosis. In this paper feasibility of application of MCSA as an automatic protection system is investigated and a new online diagnosis strategy is proposed, implemented and initially simulated to apply as an automatic system in motors fault diagnosis.